(untitled) (Global Journal of Management and Business Research, 2016)
The main aim of this case study is to assess the extent of audit findings implementation in Ethiopian public offices. Auditors express their opinion on audit finding through audit report to concerned body in each sector and design follow up mechanism for their implementation. Auditor’s opinion will bear the expected fruit only when it is fully implemented according to auditor’s recommendations. In order to assess the stage of audit findings implementation in public offices of the region, primary data was collected through Likert-scale type questionnaire from audited entities and auditors. The collected data were analyzed through simple descriptive statistics using percentage. The result of the case study revealed that there is no frequent practice of audit findings implementation in the public offices. The main causes for lack of audit findings implementation in public sectors are lack of interest for audit report; absence of integrated effort to implement audit reports; weakness in follow up; and delay in audit report presentation to audited entities.